Preparation and properties of quasi-spherical WMoTaTi refractory high entropy alloy powders - LIU Chang; CHEN Jia-nan; DING Wang-wang; YANG Jun-jun; CHEN Gang; QU Xuan-hui (Fenmo yejin jishu)
Mechanical alloying combined with the gas-solid fluidization technology was used to pre-alloy and modify the WMoTaTi elemental mixed powders to improve the powder morphology, sphericity, and flowability, basically meeting the requirements for 3D printing. X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive spectrometer (EDS) were used to characterize the surface morphology, particle size distribution, flowability, phase constituent, and chemical composition of the powders before and after fluidization. In the results, the mechanically alloyed WMoTaTi powders show the BCC single phase with good pre-alloying effect, but the sphericity of the pre-alloyed powders is only 26.7%. After the fluidization modification, the particle size distribution of the pre-alloyed powders becomes narrower, the sphericity ratio increases to 67.7%, the median diameter of WMoTaTi powders is 15.7 μm, the elemental distribution of powders is relatively uniform, the powder flowability increases to (35.3±0.2) s·(50 g)−1, and the spreading performance of powders is much better than that before fluidization, which can be used as the raw feedstock for 3D printing.